INFLUENCE OF MOTIVATION IN WORKING AND EMPLOYEES, LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE SATISFACTION (CASE STUDY PT METROPOLITAN RETAILMART) - Muhammad Apriansyah; Sinambela, Lijan P. (Pasca Sarjana Universitas Satya Negara Indonesia, 2017)
The research was conducted by using quantitative descriptive method to determine the influence of independent variables namely : motivation in working, leadership and organization culture toward the employees’satisfaction in working as the dependent variable. Samples taken are 54 respondents from the total population of 117 employees at PT.Metropolitan Retailmart, Jakarta Considering the data analysis and results of research as a whole, it can be infered that (1) there is an influence between motivation in working towards the employees’ satisfaction in working by 47,6% which the value of the correlation is 0,446 means strong in (2) There is influence of leadership towards job satisfaction Which is not significant, there is a R square value of 0.1% with a correlation value of -0.035 which means the correlation level below very low, (3) there is influence of organizational culture on job satisfaction of 30.9% with the correlation value of 0.555 which means the correlation level also Medium and (4) there is influence motivation in working , leadership and organizational culture together towards employees satisfaction equal to 53.9% with correlation value 0.752 which means strong correlation level